Bioactive Platinum(IV) Complexes Incorporating Halogenated Phenylacetates - Angelico D. Aputen; Maria George Elias; Jayne Gilbert; Jennette A. Sakoff; Christopher P. Gordon; Kieran F. Scott; Janice R. Aldrich-Wright (Molecules, 2022)
A new series of cytotoxic platinum(IV) complexes (1–8) incorporating halogenated phenylacetic acid derivatives (4-chlorophenylacetic acid, 4-fluorophenylacetic acid, 4-bromophenylacetic acid and 4-iodophenylacetic acid) were synthesised and characterised using spectroscopic and spectrometric techniques. Complexes 1–8 were assessed on a panel of cell lines including HT29 colon, U87 glioblastoma, MCF-7 breast, A2780 ovarian, H460 lung, A431 skin, Du145 prostate, BE2-C neuroblastoma, SJ-G2 glioblastoma, MIA pancreas, the ADDP-resistant ovarian variant, and the non-tumour-derived MCF10A breast line. The in vitro cytotoxicity results confirmed the superior biological activity of the studied complexes, especially those containing 4-fluorophenylacetic acid and 4-bromophenylacetic acid ligands, namely 4 and 6, eliciting an average GI50 value of 20 nM over the range of cell lines tested. In the Du145 prostate cell line, 4 exhibited the highest degree of potency amongst the derivatives, displaying a GI50 value of 0.7 nM, which makes it 1700-fold more potent than cisplatin (1200 nM) and nearly 7-fold more potent than our lead complex, 56MESS (4.6 nM) in this cell line. Notably, in the ADDP-resistant ovarian variant cell line, 4 (6 nM) was found to be almost 4700-fold more potent than cisplatin. Reduction reaction experiments were also undertaken, along with studies aimed at determining the complexes’ solubility, stability, lipophilicity, and reactive oxygen species production.